Serum-derived exomiR-188-3p is a promising novel biomarker for early-stage ovarian cancer - Wang Mingyu; Zhang Wenwen; Cheng Guangyan; Xu Juan; Qu Pengpeng (Open Medicine)
The exosomal microRNAs (exomiRNAs) are promising novel biomarkers for clinical detection and prognosis assessment of human cancers. The aim of this study was to identify potential exomiRNAs as biomarkers in ovarian cancer (OC).